Hypertension in pregnant women - Rutz-Danielczak, Aleksandra (Przewodnik Lekarza/Guide for GPs, 2006)
Prevalence of hypertension in pregnancy is approximately 5-10%. It appears to be one of more important causes of obstetric complications. Hypertension in pregnancy is recognized when blood pressure values are ≥140/90 mm Hg. Classification of hypertension in pregnancy includes: 1) chronic hypertension determined before 20 weeks of gestation; 2) pregnancy induced hypertension-determined after 20 weeks of gestation; when it is associated with proteinuria ≥300 mg per day we recognize preeclampsia; when features of intravascular hemolysis, liver damage and low platelet count are present we recognize HELLP syndrome; this state increases maternal and child mortality risk, particulary when eclampsia is overlapped; 3) pregnancy induced hypertension overlapped on chronic hypertension – when worsening of disease after 20 weeks of gestation is noticed; 4) late (transient) hypertension appears in perinatal period. The treatment of hypertension in pregnancy require special observation and close collaboration between patient and doctor. Non-pharmacological management is sufficient when blood pressure values not exceed 150/100 mmHg. In other cases we must consider pharmacological therapy with medication safe for child. After delivery verification of diagnosis and treatment is necessary.